Dominion: how the Christian revolution remade the world - Holland, Tom (Basic Books, 2019)
Part I. Antiquity. Athens : 479 BC, The Hellespont -- Jerusalem : 63 BC, Jerusalem -- Mission : AD 19, Galatia -- Belief : AD 177, Lyon -- Charity : AD 362, Pessinus -- Heaven : 492, Mount Gargano -- Exodus : 632, Carthage -- Part II. Christendom. Conversion : 754, Frisia -- Revolution : 1076, Cambrai -- Persecution : 1229, Marburg -- Flesh : 1300, Milan -- Apocalypse : 1420, Tabor -- Reformation : 1520, Wittenberg -- Cosmos : 1620, Leiden -- Part III. Modernitas. Spirit : 1649, St George's Hill -- Enlightenment : 1762, Toulouse -- Religion : 1825, Baroda -- Science : 1876, The Judith River -- Shadow : 1916, The Somme -- Love : 1967, Abbey Road -- Woke : 2015, Rostock.